ANALISIS REGRESI COX UNTUK MENENTUKAN FAKTOR-FAKTOR YANG MEMPENGARUHI LAMA STUDI MAHASISWA S1 FMIPA UNIVERSITAS LAMBUNG MANGKURAT - Tanjung, Winda Adinda; Anggraini, Dewi; Annisa, Selvi (Jurnal Gaussian, 2024)
The length of study is the time it takes a student to complete his education. One of the tertiary institutions that is trying to improve the quality of its student degrees in Indonesia is the Faculty of Mathematics and Natural Sciences, University of Lambung Mangkurat (ULM). This study aims to determine the factors that influence the length of study of ULM FMIPA undergraduate students. The analysis used to determine the effect of these factors is survival analysis through the Cox Proportional Hazard Regression method. The results of this study indicate that the Chemistry Study Program has the greatest chance of being able to complete studies ≤4 years or graduate on time compared to other Study Programs. From the process of the Cox Proportional Hazard Regression method, it was found that the factors that significantly affected the length of study of FMIPA ULM undergraduate students were Gender (Female), GPA (> 3.50) and Status of Residence (Bos/Dormitory/Lodge).